Do Primary Care Physician Perform Clinical Breast Exams Prior to Ordering a Mammogram?. Issue 2 (20th December 2015) - Larson, Kelsey E.; Cowher, Michael S.; O'Rourke, Colin; Patel, Mita; Pratt, Debra
Abstract: Both the American Cancer Society and National Comprehensive Cancer Network recommend annual clinical breast examination (CBE) along with screening mammogram (SM) for patients starting at 40 years of age. However, patients with a palpable breast mass should have a diagnostic mammogram (DM) during workup. Review at our institution demonstrated that 11% of patients with newly diagnosed breast cancer and self‐identified breast mass had SM instead of DM. This led us to question whether primary care physicians (PCP) perform CBE prior to ordering mammography. As part of the routine preimaging screening, patients were asked if they had undergone breast examination by a medical provider prior to mammogram order. Data on mammogram type, ordering physician specialty, and presence of symptoms on day of mammogram were recorded. Of 6, 109 mammograms, 4, 823 were ordered by PCPs. CBE was performed prior to 67.2% SM and 64.8% DM (p = 0.12). OB/GYN performed statistically significantly higher CBE (81.6%) compared to internal (45.4%) and family (50.5%) medicine physicians (p < 0.001). Of patients with self‐reported breast symptoms, 8.7% had SM ordered rather than DM. Despite recommendations, approximately 1/3 of women report not having CBE prior to mammogram. The chances of having a CBE varied significantly by PCP specialty. Lack of CBE can lead to incorrect type of mammogram, with possibly increased cost and delay in diagnosis. Further evaluation is needed to understand why CBE was not performed in some patients.